The Effect of Library Service Quality Management on Increasing Student Visits at SMAN 1 Taliwang Sumbawa Barat - Armansyah, Kasyandi; Hardiansyah, Hardiansyah; Najwa, Lu`luin (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2025)
This research aims to find out "The influence of managing the quality of library services on increasing student visits at SMAN 1 Taliwang, West Sumbawa." This type of research is quantitative with the variable quality of library services X and interest in visiting students as variable Y. The population and sample of this research are class students X and XI with a total sample of 86 students consisting of class X, 43, and class Data collection methods use questionnaires and documentation methods. Meanwhile, the data analysis method uses descriptive statistical analysis and simple linear regression analysis. From the correlation results with the sig value. 0.01 < 0.05 between variables The quality of library services does not have a significant effect on increasing student visits at SMAN 1 Taliwang, West Sumbawa. Rejected. Â 